MARKETING RESEARCH FOR CHOOSING THE PROMOTIONAL MESSAGE CONTENT FOR DOMESTIC ORGANIC PRODUCTS - Salai, Suzana; Sudarević, Tomislav; Pupovac, Ljubomir (Economics of Agriculture, 2018)
Choosing the content of promotional messages is a part of the activities of integrated marketing communication. As far as organic products in the world are concerned, research related to the choice of promotional message content is the object of much attention, primarily based on the conduct of research among the consumers of these product (information for defining the aim of promotion, creating and testing promotional messages, selecting media and media mix, and determining the number and frequency of promotional events). Promoting domestic organic products also inevitably implies conducting consumer-centered marketing research, in order to choose the appropriate promotional message. In this respect, this article defines several goals: study the choice of the promotional message content in relation to other activities of integrated marketing communication; consider this question in the context of relevant foreign market research into organic product consumers; determine the level of marketing research, which could be used for approaching the issue from the domestic perspective; and establish which recommendations and implication could be generated when domestic organic products are concerned.